Heat-conducting insulating coating, preparation method and lithium ion battery module
Through the insulating particle material coated with one-dimensional thermal conductivity nanofibers, an efficient thermal conductivity insulating coating is constructed, which solves the problem of low thermal conductivity of lithium-ion battery modules, improves the safety and temperature uniformity of the battery, and reduces the risk of temperature difference.
Patent Information
- Application Number
- CN202411164686.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-23
AI Technical Summary
Due to the low thermal conductivity of lithium-ion battery modules, the temperature difference between different cells increases, causing problems such as uneven aging, dendrites and internal short circuits, which increases the risk of fire and explosion.
The thermally conductive insulating particle material coated with one-dimensional thermal nanofibers is used to build a thermally conductive insulating coating through electrospinning and electrostatic spraying technology to improve thermal conductivity and insulation performance and reduce the internal temperature inhomogeneity of the battery module.
It significantly improves the thermal conductivity and insulation performance of the lithium-ion battery case, reduces the temperature difference between different cells in the battery module, and enhances the safety and operation consistency of the battery.
Smart Images

Figure BDA0005007505780000081
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of coating technology, and in particular to a thermally conductive insulating coating, a preparation method and a lithium-ion battery module. Background Art
[0002] As a new energy source with high voltage, high specific energy, long cycle life, and no pollution, lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage devices. As lithium-ion batteries occupy an increasingly larger share in the new energy market, more and more researchers are working on lithium-ion battery technology, and the requirements for lithium-ion battery performance and safety are becoming higher and higher. As the power and capacity of energy storage lithium-ion battery modules increase, the temperature difference between different cells becomes larger and larger, making it prone to uneven aging, dendrite generation, internal short circuits, and other problems, which ultimately lead to fire and explosion accidents.
[0003] At present, the outer shell of lithium-ion battery modules is covered with a layer of blue film to achieve insulation effect, but the thermal conductivity of the blue film is low and cannot eliminate the hidden dangers caused by the increase in temperature difference between different battery cells. Other conventional insulating composite materials have the problem of low thermal conductivity caused by discontinuous heat transfer channels. The battery module is also difficult to conduct the internal heat in time, and thus cannot dissipate heat through the module cooling system, causing battery failure and safety accidents.
[0004] Therefore, in order to solve the above problems, it is urgent to improve the thermal conductivity of the insulating shell of the energy storage lithium-ion battery module to reduce the temperature difference between different cells in the battery module and improve the safety of the lithium-ion battery. Summary of the invention
[0005] In order to solve the above technical problems, the present disclosure provides a thermally conductive insulating coating, a preparation method and a lithium-ion battery module. The thermally conductive insulating coating has high thermal conductivity and good stability, which can effectively improve the thermal conductivity and insulation properties of the lithium-ion battery casing, thereby improving the safety of the battery.
[0006] In a first aspect, the present disclosure provides a thermally conductive insulating coating, wherein the material of the thermally conductive insulating coating comprises insulating particles coated with one-dimensional thermally conductive nanofibers;
[0007] The one-dimensional thermally conductive nanofiber comprises a first polymer and a thermally conductive agent dispersed in the first polymer;
[0008] The material of the insulating particles includes a second polymer.
[0009] In the present disclosure, the insulating particles coated with one-dimensional thermal conductive nanofibers have good thermal conductivity and insulation. Among them, the one-dimensional thermal conductive nanofibers form a complete thermal transmission network on the surface of the insulating particles, which can promote the heat dissipation of large-capacity energy storage batteries, reduce the uneven temperature distribution inside the battery module, and improve the operating consistency and electrical performance of ion system batteries as well as safe and stable operation capabilities; at the same time, the insulating particles and one-dimensional thermal conductive nanofibers have good insulation properties to ensure battery safety.
[0010] The following are preferred technical solutions of the present disclosure, but are not intended to be limitations of the technical solutions provided by the present disclosure. Through the following technical solutions, the technical objectives and beneficial effects of the present disclosure can be better achieved and realized.
[0011] As a preferred technical solution of the present disclosure, the thermal conductor includes one or more of aluminum nitride, aluminum oxide, magnesium oxide, silicon carbide or silicon dioxide, such as a combination of aluminum nitride and aluminum oxide, a combination of aluminum oxide and magnesium oxide, a combination of silicon carbide and silicon dioxide, etc.
[0012] Preferably, the particle size of the thermal conductor is 100-1500 nm, for example, 100 nm, 200 nm, 500 nm, 800 nm, 1000 nm, 1200 nm or 1500 nm, but is not limited to the listed values, and other unlisted values within the range are also applicable, preferably 200-500 nm.
[0013] The appropriate particle size of the thermal conductor helps to improve the heat transfer effect of the one-dimensional thermal conductive nanofibers.
[0014] Preferably, the first polymer comprises one or more of polysulfone, polyethersulfone resin or polyvinyl pyrrolidone, such as a combination of polysulfone and polyethersulfone resin, a combination of polyethersulfone resin and polyvinyl pyrrolidone, a combination of polysulfone, polyethersulfone resin and polyvinyl pyrrolidone, etc.
[0015] Preferably, the mass ratio of the thermal conductor to the first polymer is (0.8-1.5):10, such as 0.8:10, 1.0:10, 1.2:10 or 1.5:10, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0016] In the present disclosure, a suitable raw material ratio helps to improve the thermal conductivity of the one-dimensional thermally conductive nanofibers. If the amount of thermally conductive agent added is too little, the thermal conductivity effect will be poor; and if too much is added, the one-dimensional thermally conductive nanofiber network cannot be effectively constructed.
[0017] As a preferred technical solution of the present disclosure, the second polymer includes a thermosetting resin.
[0018] Preferably, the particle size of the insulating particles is 100-200 μm, such as 100 μm, 120 μm, 140 μm, 160 μm, 180 μm or 200 μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0019] As a preferred technical solution of the present invention, the mass ratio of the one-dimensional thermally conductive nanofibers to the insulating particles is (0.3-0.8):10, for example, 0.3:10, 0.4:10, 0.5:10, 0.6:10, 0.7:10 or 0.8:10, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0020] In the present invention, the appropriate component ratio makes the prepared heat-conducting network more complete and has better thermal conductivity and insulation. If the content of the one-dimensional heat-conducting nanofibers is too much, the film-forming property will be poor in the later application process.
[0021] In a second aspect, the present disclosure provides a method for preparing the thermally conductive insulating coating according to the first aspect, the preparation method comprising the following steps:
[0022] mixing the thermal conductor and the first polymer with an organic solvent to obtain an electrospinning solution;
[0023] The second polymer is prepared into insulating particles by a melt extrusion granulation method;
[0024] The obtained electrostatic spinning liquid adopts the electrostatic spinning technology, and the obtained insulating particles adopt the electrostatic spraying technology, which are simultaneously sprayed on the surface of the object to be processed, and a thermal conductive insulating coating is obtained after curing.
[0025] In the present disclosure, the preparation method combines electrostatic spinning and electrostatic spraying, and under the action of the electrostatic field, one-dimensional thermal conductive fibers are coated on the surface of insulating particles to construct a rapid thermal conductive network. At the same time, through the electrostatic effect, the insulating particle coating coated with the one-dimensional thermal conductive nanofiber is sprayed on the surface of the object to be treated, and a thermal conductive insulating coating is formed after curing. The preparation method is simple and efficient, and is conducive to industrial production and application.
[0026] As a preferred technical solution of the present disclosure, the mass ratio of the thermal conductor, the first polymer and the organic solvent is (0.8-1.5):10:(40-150), for example, 0.8:10:40, 1.0:10:60, 1.0:10:80, 1.2:10:100 or 1.5:10:150, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0027] Preferably, the organic solvent comprises dimethylformamide.
[0028] As a preferred technical solution of the present disclosure, the melt extrusion granulation method comprises: melt extruding, cooling and pulverizing the second polymer or the second polymer precursor in sequence to obtain insulating particles.
[0029] Preferably, the second polymer precursor comprises a second polymer matrix and a curing agent.
[0030] The second polymer substrate reacts with the curing agent during the melt extrusion process, thereby curing to form a second polymer.
[0031] The second polymer matrix can be selected such as epoxy resin.
[0032] The curing agent may be selected from one or more of m-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylsulfone, ethylenediamine, diethylenetriamine or polyethylenepolyamine, such as a combination of m-phenylenediamine and m-phenylenediamine, a combination of ethylenediamine and diethylenetriamine, and the like.
[0033] Preferably, the mass ratio of the second polymer substrate to the curing agent is 100:(5-10), such as 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0034] As a preferred technical solution of the present disclosure, in the electrospinning technology, the voltage is 50-60kV, such as 50kV, 52kV, 54kV, 56kV, 58kV or 60kV, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0035] Preferably, in the electrostatic spraying technology, the voltage is 50-60 kV, such as 50 kV, 52 kV, 54 kV, 56 kV, 58 kV or 60 kV, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0036] Preferably, the spraying distance is 200-300 mm, for example, 200 mm, 220 mm, 240 mm, 260 mm, 280 mm or 300 mm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0037] Preferably, the curing temperature is 100-120°C, such as 100°C, 105°C, 110°C, 115°C or 120°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0038] In a third aspect, the present disclosure provides a lithium-ion battery module, comprising a battery pack housing and a battery cell encapsulated in the battery pack housing, wherein a surface of the battery pack housing is covered with a thermally conductive insulating coating as described in the first aspect or a thermally conductive insulating coating prepared as described in the second aspect.
[0039] As a preferred technical solution of the present disclosure, the thickness of the thermally conductive insulating coating is 33-100 μm, for example, 33 μm, 50 μm, 80 μm, 90 μm or 100 μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0040] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:
[0041] The thermally conductive insulating coating disclosed in the present invention overcomes the problem of low thermal conductivity caused by discontinuous heat transfer channels in conventional insulating composite material coatings, significantly improves the heat dissipation power of the battery, reduces the temperature difference between different battery cells in a large-size energy storage lithium-ion battery module, and enhances the temperature uniformity of the outer surface of the battery, thereby ensuring the consistency of the battery during operation, allowing the battery to achieve synchronous aging and not decay rapidly due to inconsistent operation; at the same time, the coating has good insulating properties, ensuring the safety of the battery. DETAILED DESCRIPTION
[0042] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.
[0043] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; obviously, the application examples in the specification are only part of the application examples of the present disclosure, rather than all of the application examples.
[0044] In a first aspect, the present disclosure provides a thermally conductive insulating coating, wherein the material of the thermally conductive insulating coating comprises insulating particles coated with one-dimensional thermally conductive nanofibers;
[0045] The one-dimensional thermally conductive nanofiber comprises a first polymer and a thermally conductive agent dispersed in the first polymer;
[0046] The material of the insulating particles includes a second polymer.
[0047] Furthermore, the thermal conductor includes one or more of aluminum nitride, aluminum oxide, magnesium oxide, silicon carbide or silicon dioxide.
[0048] Furthermore, the first polymer includes one or more of polysulfone, polyethersulfone resin or polyvinyl pyrrolidone.
[0049] Furthermore, the mass ratio of the thermal conductor to the first polymer is (0.8-1.5):10.
[0050] Furthermore, the particle size of the thermal conductor is 100-1500 nm, preferably 200-500 nm.
[0051] Furthermore, the insulating particles include thermosetting resin.
[0052] Furthermore, the particle size of the insulating particles is 100-200 μm.
[0053] In a second aspect, the present disclosure provides a method for preparing the thermally conductive insulating coating according to the first aspect, the preparation method comprising the following steps:
[0054] The thermal conductor and the first polymer are mixed with an organic solvent in a mass ratio of (0.8-1.5):10:(100-200) to obtain an electrospinning solution;
[0055] The second polymer or the second polymer precursor is sequentially melt-extruded, cooled and crushed to obtain insulating particles with a particle size of 100-200 μm;
[0056] The obtained electrospinning solution adopts electrospinning technology, and the obtained insulating particles adopt electrostatic spraying technology, and are simultaneously sprayed on the surface of the object to be treated, wherein the voltage of the electrospinning technology is 50-60kV, the voltage of the electrostatic spraying is 50-60kV, the spraying distance is 200-300mm, and after curing at 100-120°C, a 33-100μm thick thermal conductive insulating coating is formed;
[0057] Wherein, the organic solvent includes dimethylformamide.
[0058] Application Example 1
[0059] This application example provides a lithium-ion battery module, including a battery pack housing and 48 battery cells arranged in series and encapsulated in the battery pack housing; the surface of the battery pack housing is covered with a thermally conductive insulating coating; the battery pack housing is an aluminum shell;
[0060] Wherein, the preparation method of the thermally conductive insulating coating comprises:
[0061] 5 g of aluminum nitride with a diameter of 500 nm and 50 g of polyethersulfone resin (PES) were mixed with 500 g of dimethylformamide (DMF) to obtain an electrospinning solution;
[0062] 100 g of epoxy resin and 7.5 g of m-xylylenediamine were mixed, and then melt-extruded through a twin-screw extruder. The extruded flakes were cooled by a crystal drum and then crushed to obtain insulating particles with a particle size of 150 μm.
[0063] The obtained electrospinning solution adopts electrospinning technology, and the obtained insulating particles adopt electrostatic spraying technology, and are simultaneously sprayed on the surface of the aluminum shell, wherein the voltage of the electrospinning technology is 50 kV, the voltage of the electrostatic spraying is 50 kV, and the spraying distance is 250 mm, and then after curing at 100° C., a 100 μm thick thermal conductive insulating coating is formed;
[0064] In the obtained thermally conductive insulating coating, the mass ratio of the one-dimensional thermally conductive nanofibers to the insulating particles is 0.5:10.
[0065] Application Example 2
[0066] This application example provides a lithium-ion battery module, including a battery pack housing and 48 battery cells arranged in series and encapsulated in the battery pack housing; the surface of the battery pack housing is covered with a thermally conductive insulating coating; the battery pack housing is an aluminum shell;
[0067] Wherein, the preparation method of the thermally conductive insulating coating comprises:
[0068] 4 g of silicon carbide with a diameter of 200 nm and 50 g of polysulfone were mixed with 550 g of dimethylformamide (DMF) to obtain an electrospinning solution;
[0069] 100 g of epoxy resin and 10 g of 4,4'-diaminodiphenyl sulfone were mixed, and then melt-extruded through a twin-screw extruder. The extruded flakes were cooled by a crystal drum and then crushed to obtain insulating particles with a particle size of 100 μm.
[0070] The obtained electrospinning solution adopts electrospinning technology, and the obtained insulating particles adopt electrostatic spraying technology, and are simultaneously sprayed on the surface of the aluminum shell, wherein the voltage of the electrospinning technology is 50 kV, the voltage of the electrostatic spraying is 50 kV, the spraying distance is 300 mm, and then after curing at 110° C., a 80 μm thick thermal conductive insulating coating is formed;
[0071] In the obtained thermally conductive insulating coating, the mass ratio of the one-dimensional thermally conductive nanofibers to the insulating particles is 0.8:10.
[0072] Application Example 3
[0073] This application example provides a lithium-ion battery module, including a battery pack housing and 48 battery cells arranged in series and encapsulated in the battery pack housing; the surface of the battery pack housing is covered with a thermally conductive insulating coating; the battery pack housing is an aluminum shell;
[0074] Wherein, the preparation method of the thermally conductive insulating coating comprises:
[0075] 6 g of silicon carbide with a diameter of 400 nm and 50 g of polysulfone were mixed with 600 g of dimethylformamide (DMF) to obtain an electrospinning solution;
[0076] 100 g of epoxy resin and 5 g of ethylenediamine were mixed, and then melt-extruded through a twin-screw extruder. The extruded flakes were cooled by a crystal drum and then crushed to obtain insulating particles with a particle size of 200 μm.
[0077] The obtained electrospinning solution adopts electrospinning technology, and the obtained insulating particles adopt electrostatic spraying technology, and are simultaneously sprayed on the surface of the aluminum shell, wherein the voltage of the electrospinning technology is 55kV, the voltage of the electrostatic spraying is 55kV, and the spraying distance is 200mm, and then after curing at 100°C, a 33μm thick thermal conductive insulating coating is formed;
[0078] In the obtained thermally conductive insulating coating, the mass ratio of the one-dimensional thermally conductive nanofibers to the insulating particles is 0.3:10.
[0079] Comparative application example 1
[0080] This comparative application example provides a lithium-ion battery module, which refers to application example 1, except that: the coating on the surface of the battery pack housing is an insulating coating;
[0081] The method for preparing the insulating coating comprises:
[0082] 100 g of epoxy resin and 7.5 g of m-xylylenediamine were mixed, and then melt-extruded through a twin-screw extruder. The extruded flakes were cooled by a crystal drum and then crushed to obtain insulating particles with a particle size of 150 μm.
[0083] The obtained insulating particles were sprayed on the surface of the aluminum shell by electrostatic spraying technology, wherein the voltage was 50 kV and the spraying distance was 250 mm, and then cured at 100° C. to form an insulating coating with a thickness of 100 μm.
[0084] The battery modules used in the above application examples and comparative application examples are exactly the same.
[0085] The thermal conductivity of the coating on the surface of the battery pack housing in Application Examples 1-3 and Comparative Application Example 1 was measured respectively, and the results are shown in Table 1.
[0086] Table 1
[0087]
[0088]
[0089] It can be seen from Table 1 that the thermally conductive insulating coating disclosed in the present invention has good thermal conductivity, and the thermal conductivity can reach 0.651 W·m -1 ·K -1 above.
[0090] The temperature differences inside the battery modules of the lithium-ion battery modules obtained in Application Examples 1-3 and Comparative Application Example 1 under 1P operating conditions were measured, as shown in Table 2.
[0091] The rated voltage of a single battery cell in the lithium-ion battery module is 3.2V, the capacity is 280Ah, and the charging and discharging power of the lithium-ion battery module is 21.5kW.
[0092] The specific test method includes: for each battery cell, NTC thermistors are pasted on the surface, middle and bottom of the cell respectively, and the data fed back by the NTC thermistors are recorded at the end of a charge and discharge cycle. The specific temperature is calculated by the temperature-resistance formula, and the highest and lowest temperatures in the obtained temperature data are determined. The temperature difference is the difference between the highest and lowest temperatures.
[0093] Table 2
[0094] Temperature difference / ℃ Application Example 1 4.3 Application Example 2 3.9 Application Example 3 3.9 Comparative application example 1 6.5
[0095] Since the one-dimensional heat-conducting nanofibers provide a good heat-conducting channel, the uniformity of the battery temperature distribution can be effectively improved. As can be seen from Table 2, the aluminum shell with the heat-conducting insulating coating described in the present disclosure has good thermal conductivity, and under the 1P operating condition, the temperature difference of different battery cells in the energy storage lithium-ion battery module can be controlled within 4.3°C. Furthermore, silicon carbide is expensive, and under the same temperature difference conditions, aluminum nitride has good economy and high cost performance.
[0096] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0097] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A thermally conductive insulating coating, It is characterized in that The material of the thermally conductive insulating coating comprises insulating particles coated with one-dimensional thermally conductive nanofibers; The one-dimensional thermally conductive nanofiber comprises a first polymer and a thermally conductive agent dispersed in the first polymer; The material of the insulating particles includes a second polymer.
2. The thermally conductive insulating coating according to claim 1, It is characterized in that The thermal conductor includes one or more of aluminum nitride, aluminum oxide, magnesium oxide, silicon carbide or silicon dioxide; Preferably, the particle size of the thermal conductive agent is 100-1500 nm, preferably 200-500 nm; Preferably, the first polymer comprises one or more of polysulfone, polyethersulfone resin or polyvinyl pyrrolidone; Preferably, the mass ratio of the thermal conductor to the first polymer is (0.8-1.5):
10.
3. The thermally conductive insulating coating according to claim 1 or 2, It is characterized in that The second polymer comprises a thermosetting resin; Preferably, the particle size of the insulating particles is 100-200 μm.
4. The thermally conductive insulating coating according to any one of claims 1 to 3, It is characterized in that The mass ratio of the one-dimensional thermally conductive nanofibers to the insulating particles is (0.3-0.8):
10.
5. A method for preparing a thermally conductive insulating coating according to any one of claims 1 to 4, It is characterized in that The preparation method comprises the following steps: mixing the thermal conductor and the first polymer with an organic solvent to obtain an electrospinning solution; The second polymer is prepared into insulating particles by a melt extrusion granulation method; The obtained electrostatic spinning liquid adopts the electrostatic spinning technology, and the obtained insulating particles adopt the electrostatic spraying technology, which are simultaneously sprayed on the surface of the object to be processed, and a thermal conductive insulating coating is obtained after curing.
6. The preparation method according to claim 5, It is characterized in that The mass ratio of the thermal conductor, the first polymer and the organic solvent is (0.8-1.5):10:(40-150); Preferably, the organic solvent comprises dimethylformamide.
7. The preparation method according to claim 5 or 6, It is characterized in that The melt extrusion granulation method comprises: melt extruding, cooling and pulverizing the second polymer or the second polymer precursor in sequence to obtain insulating particles.
8. The preparation method according to any one of claims 5 to 7, It is characterized in that In the electrospinning technique, the voltage is 50-60 kV; Preferably, in the electrostatic spraying technology, the voltage is 50-60 kV; Preferably, the spraying distance is 200-300 mm; Preferably, the curing temperature is 100-120°C.
9. A lithium-ion battery module, comprising a battery pack housing and a battery cell encapsulated in the battery pack housing, It is characterized in that The surface of the battery pack shell is covered with the thermally conductive insulating coating according to any one of claims 1 to 4 or the thermally conductive insulating coating prepared by the preparation method according to any one of claims 5 to 8.
10. The lithium-ion battery module according to claim 9, It is characterized in that The thickness of the thermally conductive insulating coating is 33-100 μm.
Citation Information
Patent Citations
Preparation method of tensile strain sensor with high thermal conductivity
CN110306354A
Insulating heat-conducting coating of lithium ion battery pole piece and preparation method of insulating heat-conducting coating
CN112701243A
Insulating and cooling composite film
CN112820485A
Insulating powder coating and application thereof
CN112898871A
Modified composite diaphragm and preparation method thereof
CN116315437A
